A combination of eye-gaze and head-gaze interactions improves efficiency and user experience in an object positioning task in virtual environments. (September 2022) - Deng, Cheng-Long; Tian, Chen-Yu; Kuai, Shu-Guang
Abstract: Eye-gaze and head-gaze are two hands-free interaction modes in virtual reality, each of which has demonstrated different strengths. Selecting suitable interaction modes in different scenarios is important to achieve efficient interaction in virtual scenes. This study compared the movement time in an object positioning task by examining eye-gaze interaction and head-gaze interaction in various conditions. In turn, it identified the superior zones for each mode, respectively. Based on this information, we designed a combination mode – utilizing eye-gaze interaction at the acceleration phase and deceleration phase and head-gaze interaction at the correction phase – to achieve the optimal interaction mode, which has allowed us to obtain higher efficiency and subjective satisfaction. This study provides a comprehensive analysis of the characteristics of the eye-gaze and head-gaze interaction modes and provides valuable insights into selecting the appropriate interaction modes for virtual reality applications. Highlights: Eye-gaze interaction and head-gaze interaction demonstrate different advantages. Eye-gaze interaction is more efficient in the acceleration and deceleration phases. People perform better in the correction phase using head-gaze interaction. There are superior zones for eye-gaze and head-gaze interactions, respectively. A combination interaction mode leads to higher efficiency and better user experience.